2023
DOI: 10.3390/biomedicines11082267
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Interaction between Exercise, Gut Microbiota, and Neurodegeneration: Future Research Directions

Abstract: Physical activity has been demonstrated to have a significant impact on gut microbial diversity and function. Emerging research has revealed certain aspects of the complex interactions between the gut, exercise, microbiota, and neurodegenerative diseases, suggesting that changes in gut microbial diversity and metabolic function may have an impact on the onset and progression of neurological conditions. This study aimed to review the current literature from several databases until 1 June 2023 (PubMed/MEDLINE, W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 141 publications
(166 reference statements)
0
6
0
Order By: Relevance
“…Age, diet, lifestyle, environment, and disease may also account for individualized differences since they can shape and alter the gut’s microbial composition [ 15 ]. Furthermore, studies have shown that dietary changes or acute lifestyle modifications can quickly and reproducibly alter the gut microbiota [ 19 , 20 , 21 ]. Over the past decade, the relationship between gut health and neurological disorders has become a subject of research interest.…”
Section: Evidence Of Gut Dysbiosis In Human Amyotrophic Lateral Scler...mentioning
confidence: 99%
“…Age, diet, lifestyle, environment, and disease may also account for individualized differences since they can shape and alter the gut’s microbial composition [ 15 ]. Furthermore, studies have shown that dietary changes or acute lifestyle modifications can quickly and reproducibly alter the gut microbiota [ 19 , 20 , 21 ]. Over the past decade, the relationship between gut health and neurological disorders has become a subject of research interest.…”
Section: Evidence Of Gut Dysbiosis In Human Amyotrophic Lateral Scler...mentioning
confidence: 99%
“…The proliferation of lactate-metabolizing bacteria in the gut may be impacted by circumstances in which lactate levels are elevated [ 148 , 149 ]. This interaction between lactate levels and gut microbiota is observed in various populations, including obese individuals and highly trained athletes [ 150 ]. Lactate can be metabolized by Veillonella atypica , the Eubacterium hallii group, Anaerobutyricum hallii , Anaerostipes, and numerous other bacterial species, producing SCFAs and other intermediates that, following an exercise period, enrich particular bacterial populations and add to microbial diversity [ 150 ].…”
Section: A Healthy Gut Microbiomementioning
confidence: 99%
“…Similarly, there are correlations between exercise performance and metabolomic propionic acid production along with other short chain fatty acids (SCFAs) (Muccioli et al, 2010;Sales and Reimer, 2023). Other studies illustrate connections between physical activity and increased microbiota metabolomic representation of tricyclic acid cycle genes (Rojas-Valverde et al, 2023), glycolysis and oxidative phosphorylation which directly enhance host metabolic performance and capacity (Hintikka et al, 2023). Lastly, analgesic effects of exercise, effecting tolerance, are also shown to be potentially dependent on microbial communities, such as those that stimulate peripheral cannabinoid receptor 1 (CB1)-mediated signaling (Koltyn et al, 2014).…”
Section: Introductionmentioning
confidence: 99%